Convenient Access to Ester‐Containing Quinolinones through a Sequential Radical Alkoxycarbonylation/Cyclization/Hydrolysis Process. Issue 2 (20th January 2022) - Guo, Sa; Wang, Xin; Zhao, Dongyang; Zhang, Zhiguo; Zhang, Guisheng; Tang, Shi; Sun, Kai
Abstract: Here, we report a sequential radical alkoxycarbonylation/cyclization/hydrolysis reaction with carbazates as eco‐friendly ester sources. Various structurally diverse ester‐substituted quinolinones were obtained in moderate to high yields. Easy scale‐up operation and the potential for product derivatization, such as hydrolysis, reduction and dealkylation, make this method attractive for the preparation of other valuable ester‐containing N ‐heterocycles. Mechanistic studies suggest that the catalytic system involves a radical pathway. Abstract : A practical protocol for the efficient synthesis of a series of structurally diverse ester‐substituted quinoline‐2, 4‐diones through sequential alkoxycarbonylation/addition/cyclization/hydrolysis with carbazates as eco‐friendly ester sources was developed.